Formulation, Characterization, and Optimization of a Better and Novel Transfersome Formulation Containing Olmesartan Using Design-Expert 11 Software - Anitha, P. (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present study was aimed to optimize, formulate, and characterize a better and novel transferosome formulation containing olmesartan (OS). Materials and Methods: The preformulation studies were performed by Fourier transform infrared spectrophotometer. OS transferosome gel was fabricated and optimized asper Design Expert 11 Software. A three-factor, three-level, Box–Behnken design was applied to optimize transfersome formulation, using response surface methodology. The amount of phospotidyl choline 90 G (PC 90G) (A), surfactant (B), and sonication time (C) were selected as independent variables. The OS optimized formulation was evaluated for Scanning Electron Microscopy (SEM), Entrapment efficiency (EE) (PDE), and in vitro studies. The ANOVA was done for EE and in vitro studies. Results and Discussion: Optimized formulation prepared with phospholipid (A) 451.84 mg, Surfactant (B) 144.93 mg, sonication time (C) 6 min. It was evaluated for EE and in vitro drug release and values were found to be in close agreement with the predict values. In vitro studies confirmed that release of OS for >24 h. It was found to be spherical from SEM analysis. Conclusion: Hence, in the prepared transferosome formulation, phospholipid and surfactant were effectively working for prolonged delivery of OS.